2021
DOI: 10.1007/s11252-021-01160-0
|View full text |Cite
|
Sign up to set email alerts
|

Tick infestation of birds across a gradient of urbanization intensity in the United States Great Plains

Abstract: Migratory birds play an important role in large-scale movements of ticks and tick-borne pathogens, yet little is known about tick infestation of resident birds (e.g., non-migratory species and migratory species during the breeding season), especially in urban ecosystems. We captured birds during the breeding season in parks and greenspaces in Oklahoma City, Oklahoma, USA, to evaluate overall tick infestation patterns and to determine if urbanization influences infestation prevalence (the proportion of birds pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…This lack of significant association of deer with A. americanum abundance suggests that other hosts, such as birds, mesomammals (raccoons), or small mammals, may be just as important to the distribution and abundance of A. americanum in urban areas. Support for this hypothesis is provided by a companion study conducted in the same 16 parks; this study found that at least 24% of birds carried at least 1 tick, and that A. americanum comprised 51% of all ticks found on birds (Roselli et al 2022). The current study only evaluated deer abundance during 1 season.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This lack of significant association of deer with A. americanum abundance suggests that other hosts, such as birds, mesomammals (raccoons), or small mammals, may be just as important to the distribution and abundance of A. americanum in urban areas. Support for this hypothesis is provided by a companion study conducted in the same 16 parks; this study found that at least 24% of birds carried at least 1 tick, and that A. americanum comprised 51% of all ticks found on birds (Roselli et al 2022). The current study only evaluated deer abundance during 1 season.…”
Section: Discussionmentioning
confidence: 92%
“…Past research on I. scapularis in urban areas suggests that abundance of this vector tick species may decrease with increasing urbanization (Jobe et al 2007, Rydzewski et al 2012, Diuk-Wasser et al 2021), while other studies of A. americanum and A. maculatum also show the same lack of association with urbanization that we found for these species (Fornadel et al 2011, Blanton et al 2014, Noden et al 2017). These species-specific patterns may reflect varying levels of adaptability to the abiotic conditions and vegetation and host communities associated with urban areas; different movements, habitat use, and thus, patterns of association with urban landscapes for each species' primary wildlife hosts (Roselli et al 2022); and/ or differences in tick detectability across the urban development gradient (i.e., ticks harder to detect when they occur in highly urbanized areas). For D. variabilis , populations in rural areas are known to be highly clustered and most commonly found in agricultural areas (Trout-Fryxell et al 2015); therefore, we hypothesize that this species' negative association with urban development in our study could reflect a lack of suitable, agricultural habitat in highly urbanized landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, an extremely dense population of some species in cities can have negative effects on human health, economy, and food production. Haaksma et al (2022) given that avian influenza affects all birds, particularly migratory birds (Lycett et al 2019); parasites can be transferred from Rock pigeon (Al-Barwari and Saeed 2012); House sparrow can be infested by ticks (Roselli et al 2022); and filth (Eurasian tree sparrow, Eastern jungle crow, Rock pigeon, Whitevened Myna, etc.). When compared to forest birds, urban birds showed more investigative behavior, antagonism, and a faster breathing rate (Caizergues et al 2022), including different behavior due to variations in food and preferences (Tryjanowski et al 2011;Lowry et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the host-specific nature of most ectoparasites, regional host-ectoparasite relationships are difficult to identify for many wildlife hosts because of challenges involved in collecting from live animals. Many studies use mist-netting (Cerutti et al 2018, Roselli et al 2022), but they collect only certain orders of birds, leaving most bird species unavailable because they often involve complicated trapping techniques and specific permits. Live-animal trapping is commonly used for wild animals, but current studies trap one or two host species as part of a larger focus (Pirrello et al 2015, Bezerra-Santos et al 2021, Levesque-Beaudin and Sinclair 2021 or continue to use randomness of roadkill or road injury cases to obtain samples (McAllister et al 2018(McAllister et al , 2019Lavallée et al 2020).…”
Section: Strigiformes: Barred Owl (Strix Varia Bartonmentioning
confidence: 99%